2021
DOI: 10.11622/smedj.2020159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers on in-hospital mortality among patients with COVID-19: a systematic review and meta-analysis

Abstract: INTRODUCTION There are concerns that angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) may worsen the outcomes of patients with COVID-19. This systematic review and meta-analysis aimed to study the in-hospital mortality among COVID-19 patients who were on ACEIs/ARBs as compared to those not on ACEIs/ARBs. METHODS We searched PubMed, EMBASE, clinicaltrials.gov and Google Scholar between 1 January 2020 and 30 May 2020 to identify all studies that evaluated the use of ACEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 26 publications
(67 reference statements)
0
20
0
1
Order By: Relevance
“…Retrospective observational studies are marked by bias and other methodologic concerns so the overall neutral findings are of limited value [ 14 21 ]. Two recent meta-analyses have shown no benefit or harm of ARBs in COVID-19 [ 22 , 23 ]. Interestingly, however, ACE-I and ARBs have been documented to be lung protective, suggesting possible benefit in renin angiotensin system blockade in pneumonia [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective observational studies are marked by bias and other methodologic concerns so the overall neutral findings are of limited value [ 14 21 ]. Two recent meta-analyses have shown no benefit or harm of ARBs in COVID-19 [ 22 , 23 ]. Interestingly, however, ACE-I and ARBs have been documented to be lung protective, suggesting possible benefit in renin angiotensin system blockade in pneumonia [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 At least 52 meta‐analyses have assessed associations between RAAS inhibitor use and COVID‐19 risk by collating parts of that body of research. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 However, little attention has been paid to selection bias, or other biases for that matter, which may distort the interaction between RAAS inhibitor use and COVID‐19.…”
mentioning
confidence: 99%
“…In terms of number of COVID-19 related outcomes reported in each review, one outcome was reported by 13 reviews (27.7%) (18, 20, 21, 23, 24, 28, 29, 38, 39, 47, 52, 53, 61), two outcomes by 15 reviews (31.9%) (4, 17, 26, 31, 32, 34-37, 40, 42, 49, 54, 55, 58), three outcomes by 11 reviews (23.4%) (6, 22, 25, 27, 33, 44-46, 50, 56, 60) and 4-9 outcomes by eight reviews (17%) (19, 30, 41, 43, 48, 51, 57, 59). Overall, the 47 eligible reviews reported data on 18 unique pooled outcome estimates including death in 36 reviews, reviews (4, 6, 17-19, 22, 24, 25, 27, 30-39, 41-49, 54-56, 58-60), ICU admission in nine reviews (27, 28, 30, 41, 43, 48, 51, 56, 59), death/ICU admission as a composite outcome in 16 reviews (4, 20, 21, 23, 26, 29, 31, 32, 40, 41, 43, 45, 51, 55, 59), risk of acquiring COVID-19 infection in 15 reviews (19, 25, 27, 40<...>…”
Section: Resultsmentioning
confidence: 99%
“…were published in a pre-print database) (17-19, 21-23, 30, 32-34, 36, 46, 50, 54, 60). The time the searches were conducted ranged from April 2020 to October 2020, with 21 (44.7%) review searches conducted in the month of May 2020 (4-6, 17, 21, 23, 24, 28, 30-32, 35, 36, 40-42, 44, 46, 48, 50, 54) Pre-print articles were included in 28 (59.6%) reviews (4, 17, 19-22, 25, 26, 30, 33, 37, 41-45, 47-53, 55, 56, 59, 60), and 10 (21.3%) reviews adjusted for retracted studies (4, 18, 31, 40, 45, 47-50, 56). Full details of the 47 reviews are presented in Supplementary file 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation